Effectiveness of Orem's Theory-Based Diabetic Foot SPA on Glycemic Control and Peripheral Neuropathy in Type 2 DM - Ni Luh Putu Ayu Puspita Wangi; Ni Luh Putu Inca Buntari Agustini; Sri Dewi Megayanti; Yustina Ni Putu Yusniawati; Jintana Artsanthia (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Type 2 DM remains a challenge both globally and nationally, due to the high incidence of diabetic foot ulcers and patients with uncontrolled glycemia. This is due to poor self-care for foot care and glycemic control. Not treating them quickly will increase lifelong disability, depression, quality of life, and risk of death. Diabetic foot spa based on Orem Theory was tested for glycemic management and peripheral neuropathy in type 2 DM patients. The purpose of this study was to determine the effectiveness of diabetic foot spa based on Orem's Theory on glycemic control and reduction of peripheral neuropathy symptoms in patients with type 2 DM in the work area of East Denpasar Health Center I. This study used a pre-post quasi-experimental design with a control group of 64 respondents with a diagnosis of type 2 DM consisting of 32 control groups given foot exercises and 32 intervention groups given diabetic foot spa. Translated with DeepL.com (free version) Glucose meter, neuropathy symptom score (NSS) questionnaire, and 10 mg monofilament were used. This study consisted of univariate and bivariate analysis. Bivariate analysis used Dependent and Independent t-test to see the difference before and after diabetic foot spa intervention. The results showed that the effectiveness of diabetic foot spa in the intervention and control groups using independent t-test obtained a p-value <0.05 which states that diabetic foot spa is effective in controlling glycemia and reducing peripheral neuropathy in patients with type 2 DM. The conclusion of this study is that diabetic foot spa based on Orem's Theory is effective in controlling glycemic and reducing symptoms of peripheral neuropathy in patients with type 2 DM.